Optimal fibre architecture of soft-matrix ballistic laminates. (February 2016) - K., Karthikeyan; Kazemahvazi, S.; Russell, B.P.
Highlights: A new methodology is proposed for characterisation of lay-ups. Local failure is shown to be related to inter-ply angle. Global failure is shown to be related to anisotropy of lay-up. Pull-out is demonstrated to have a first order effect on penetration velocity. Graphical Abstract: Abstract: Soft-matrix ballistic laminates (such as those composed of fibres of Ultra High Molecular-Weight Polyethylene, e.g. Dyneema ® HB26 and Spectra Shield) find extensive use as catching type armour systems. The relationship between the lay-up of these laminates with respect to the observed failure mechanisms has not been empirically investigated in the open literature, and is the subject of this work. Lay-ups are characterised by two parameters: (i) sequencing (or interply lay-up angle) θ ¯ and (ii) in-plane anisotropy β, and can be mapped on to θ ¯ – β space. Four geometries that lie at the extrema of this parameter space are designed, built and tested. Testing is through ball bearing impact on circular clamped plates. The anisotropy ( β ) is coupled to the macroscopic response of the plates, while sequencing ( θ ¯ ) is coupled to the microscopic response. Penetration velocity is strongly affected by pull-out at the boundary, and in the present study this is shown to account for two-thirds of the ballistic resistance. The results have implications for validation testing on scaled samples, predictive modelling and simulation, and armour design.